EFEK EKSTRAK KULIT UMBI BAWANG PUTIH (Allium sativum L.) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA TIKUS PUTIH JANTAN GALUR WISTAR YANG DIINDUKSI ALOKSAN - Rina Wijayanti; Abdur Rosyid (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2015)
ABSTRACT Bulbs of garlic has been used as a traditional medicine. The use of garlic bulbs waste leaves tuber skin that has not been used optimally. This study aims to determine the content of the active compound and the effects of skin garlic bulbs extract (Allium sativum L) on blood glucose levels in male rats wistar strain induced alloxan. The subject of research in the form of 25 white male rats who were divided into 5 groups, group I are group fed a standard baseline; group II, III, IV and V Alloxan induced a dose of 160 mg/kgBW by intraperitoneal; group III, IV, and V are given skin garlic bulbs extract each with a dose of 200 mg/200gBW, 400 mg/200gBW, and 800 mg/200gBW orally for 14 days. Data obtained from the examination of blood glucose levels and analyzed using Kruskal-Wallis and Mann-Whitney. The results showed that skin garlic bulbs extract contains the active compounds alkaloid, quinones, flavonoids, saponins and polyphenols. Analysis of the data showed that there were significant differences in blood glucose levels between groups I with II, and group II with V. Conclusion, skin garlic bulbs extract (Allium sativum L) has the ability to lower blood glucose levels in mice induced by a decrease alloxan means the dose of 800 mg / 200gBW. Keywords: Skin garlic bulbs extract, Blood GlucosePENDAHULUANDiabetes Mellitus (DM) merupakan penyakit yang